Professional Human Resources to Create Consumer Satisfaction and The Impact on Purchasing Intention. - Zahera Mega; Jubery Marwan (Program Studi S3 Ilmu Manajemen, 2022)
Knowledge and skills possessed by individuals will lead to behavior. Meanwhile, the behavior will produce performance. A person's ability, both knowledge or skills possessed in carrying out work will encourage them to perform well. Individual aspects related to individual abilities and work professionalism, group aspects related to the environment in which they work; such as discipline, job compensation, and job satisfaction as well as aspects of the organizational system related to the extent to which the employee adheres to a commitment to growing the company. The responsibility of human resource management in carrying out their duties is to be able to provide suitable substrates for talented and capable personnel in the organization such as; individual ability, work professionalism, organizational commitment, work discipline, work compensation, and job satisfaction so that they can carry out their duties with good quality. Thus, according to the results and objectives of this study, professional human resources can directly create consumer satisfaction and its impact on purchasing intention. This type of research is explanatory research with a quantitative approach. To test the developed hypothesis using path analysis. Data were obtained from the results of distributing questionnaires to culinary tourism actors using a survey method. The sampling technique used the entire population as a sample (census) with a Likert scale. Primary data analysis was carried out after testing the validity and reliability and normality of the data. Keyword : Customer Satisfaction, Purchasing Intention, Professional Human Resources.